Pelatihan Penggunaan Euphorbia hirta untuk Pengobatan Ikan yang Terinfeksi Bakteri di Noekele - Immaria Fransira; Yudiana Jasmanindar; Asriati Djonu; Elfrida Susmita; Theofilia Hermana Lembunai; Monika Karnini Emba; Yohanes Anggi Bony; Jefrianus Nggadu; Marlon Nifu; Yuliana Salosso (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Bacterial infection is a problem often faced by farmers in Noekele. Treatment of fish infected with bacteria so far has mostly used antibiotics, which can lead to resistance in fish. An alternative is to use natural ingredients, one of which is Euphorbia hirta or patikan kerbau. Therefore, it is necessary to conduct training related to the use of E. hirta as a fish treatment for farmers in Noekele. The purpose of the training is to improve the skills of Noekele farmers regarding the use of E. hirta for the treatment of fish infected with bacteria through the training provided, so that it will have an impact on the process of fish farming. The methods used in this training activity were lectures, demonstrations, and discussions. The implementation of the activity went smoothly from start to finish. This training provides additional knowledge and skills related to how to make E. hirta boiled extract and its simple application, very efficient to be done by farmers.